DNA profiling among egg and beef meat isolates of Escherichia coli by enterobacterial repetitive intergenic consensus-PCR (ERIC-PCR) and random amplified polymorphic DNA-PCR (RAPD-PCR) - Abd Mutalib, Sahilah; L. Y. Y., Audrey; Ong, S. L.; Wan Nazri, Wan Sakeenah; Shahimi, Safiyyah; Abdullah Sani, Norrakiah; Abdullah, Aminah; Ariffin, Ahmad Azuhairi (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
Forty three (n=43) genomic DNA of Escherichia coli (11 isolates from eggs and 32 isolates from imported beef meats) were characterized by shiga toxin 1 (stx1), enterobacterial repetitive intergenic consensus-PCR (ERIC-PCR) and random amplified polymorphic DNA-PCR (RAPD-PCR) analyses. In the shiga toxin 1 (stx1) gene detection with primer stx 1F (5'-TTCTTCGGTATCCTATTCCC-3') and stx 1R (5'- CTGTCACAGTAACAACCGT-3'), 9 E. coli of beef meats isolates were positive toward sxt1 gene. The results of the ERIC-PCR and RAPD-PCR were analyzed using GelCompar II software. ERIC-PCR with primer ERIC1 (5'-CACTTAGGGGTCCTCGAATGTA -3') and ERIC2 (5'-AAGTAAGTGACTGGGGTGAGCG-3') discriminated the E. coli into 6 clusters and 10 single isolates at 80% similarity. RAPD-PCR with primer Gen8 and Gen9, produced 10 clusters and 15 single isolates and 12 clusters and 14 single isolates of 80%, respectively. These results demonstrated that both ERIC-PCR and RAPD-PCR are useful and suitable tools for molecular typing of those isolates examined.